Development of pupil divided optics with magnification correction for high NA oblique imaging. (1st December 2022) - Arima, Eiji; Urano, Yuta; Honda, Toshifumi; Matsumoto, Shunichi
Abstract: For manufacturing semiconductor devices and hard disks, a high sensitivity and high throughput inspection system is required to detect defects on the surface of semiconductor wafers or disk substrates. Dark-field optical microscopy with high numerical-aperture detectors in oblique directions is often used to detect weak and anisotropic scattered light from small defects. With conventional high numerical aperture (NA) optics, it is difficult to image the wide field from an oblique direction because of its short depth of focus (DOF). Here, we propose a new optics called "pupil divided optics with magnification correction." In this optics, a low NA cylindrical lens array is placed on the pupil plane of the high NA objective lens to extend DOF. In this paper, we describe the theory and configuration of the proposed optics. Our simulation and experimental results show the capability for oblique imaging with a wide field.